Third-generation prospect theory - Ulrich Schmidt; Chris Starmer; Robert Sugden (Journal of Risk and Uncertainty, 2008)
We present a new theory of decision under uncertainty: third-generation prospect theory (PT3). This retains the predictive power of previous versions of prospect theory, but extends that theory by allowing reference points to be uncertain while decision weights are specified in a rank-dependent way. We show that PT3 preferences respect a state-conditional form of stochastic dominance. The theory predicts the observed tendency for willingness-to-accept valuations of lotteries to be greater than willingness-to-pay valuations. When PT3 is made operational by using simple functional forms with parameter values derived from existing experimental evidence, it predicts observed patterns of the preference reversal phenomenon.
Keywords: D81; 330; Prospect theory; Preference reversal; Reference dependence; Prospect Theory; Entscheidung bei Unsicherheit